OPTIMIZATION OF BIODIESEL PRODUCTION FROM USED OIL OF FISH PROCESOR USING SODIUM METHOXIDE AND SULPHONATED EGG-SHELLS AS CATALYST - Ayatullahi, S. M.; Muhammad, C.; Sokoto, A. M.; Mamuda, M.; Yusuf, M. M.; Muhammad, A. U. (FUDMA JOURNAL OF SCIENCES, 2023)
Finding a long-term solution to the world’s growing dependence on conventional energy sources and the depletion of fossil fuels is what worries scientists the most right now. An alternative that appears promise is biodiesel. It was investigated how to increase the generation of biodiesel from leftover fish processors’ oil using sodium methoxide and sulphonated eggshells as a catalyst, based on Box-Behnken design. The greatest yield of 96.81% was achieved at 1:12 oil to methanol ratio, 65 °C reaction temperature, 90 minutes, and 0.5 w/w% catalysts loading. The variables constant, methanol to oil ratio, reaction temperature, reaction time, reaction temperature* reaction temperature, and methanol to oil ratio*catalyst load all had a significant effect on the biodiesel production, according to the response surface regression. The model does a good job of accounting for the link between biodiesel and process variables. Thus, residual fish processor oil might be effectively converted into more advantageous and environmentally benign biodiesel fuel.